IMPROVING ECONOMIC RESILIENCE BASED ON THE VALUE OF AMARE CULTURE - Januari Ayu Fridayani (Management and Sustainable Development Journal, 2019)
The purpose of this research is to contribute to the border area in order to improve the economy, as one of the pillars of national security. This research was conducted in Bengkayang which is one of the regency areas in West Kalimantan. It is directly adjacent to Sarawak, Malaysia. The method used in this study is a qualitative method by carrying out focus group discussions. The material used is about financial literacy and financial behavior as one of the efforts that can be done to improve the economic resilience of a region. The target of this study is housewives, because housewives are important figures in managing family finances. The added value highlighted in this study is the existence of aspects of spirituality that are adapted to the beliefs held by the group studied and synergized in the provision of material, namely the value of amare culture. The results of this study were found to be a phenomenon that although in border areas, the community had received financial literacy education, however it did not get a good response, a lack of implementation of financial literacy had an impact on negative financial behavior patterns, when knowing that financial literacy can be used as a means of manifesting the faith adopted by enthusiastic housewives and giving a positive response.